Agroforestry for natural resource management: An alternative agriculture - Malik, H.A.; Jan, Nusrat (Indian Journal of Agroforestry, 2020)
The 53rd National Development Council (NDC) resolution resolves that agricultural development strategies must be reoriented and reaffirms its commitment to achieve 4 percent annual growth rate in the agricultural sector during the Eleventh Plan. However, the stipulated overall growth rate during this period can not be achieved with the ongoing shrinking and degradation of the Country's natural resources. Planning Commission has constituted a Working Group for Eleventh Plan (2007-12) to suggest suitable recommendations on the complex issues confronting Natural Resource Management (NRM). Conservation of natural resources in India is linked to the conservation of livelihoods resources. In India, per capita forest area is only 0.064 ha against the world average of 0.64 hectares. The productivity of our forests is only 1.34 m3/ha/year against the world average of 2.1 m3/ha/year. Report of the Forest Survey of India 2003, indicates that the country now has only 67.83 m ha of forest (tree canopy) cover i.e. 20.64 percent of the land area against the Forest Policy requirement of 33 percent. Conservation of natural resources is therefore essential for sustainability of livelihoods of 2/3rd of the nation besides contributing to environmental sustainability. The gap between present demand for timber, fuel and fodder and availability is a major concern. The demand supply scenario reflects that there is an urgent need for initiating effective policies and adequately funded programmes for conservation, regeneration, and sustainable use of forests as well as a massive agroforestry effort under all natural resource development oriented programmes. The relationship between agroforestry and natural resource management seems to be indispensable, interwoven and completely interlocked. Productivity can be optimized only by augment afforestation, conservation, participatory management and optimum utilization of available resources. Green cover is indicator of resilience of the natural resources and a primary requirement for sustainable agriculture production. Agroforestry characterized by the integration of agriculture and forestry to enhance the production and productivity, leading to increase in farm income while maintaining the sustainability of farming system. The agroforestry is known to have the potential to moderate the climate which is the major cause of concern through out the world. The growing food insecurity and deteriorating livelihood situations call for concerted and consorted actions at national and international levels. This paper reviews the whole gamut of issues related with agroforestry particularly in context of natural resource management, constraints, major initiatives taken by the Government of India in this direction. Financial implications during the Eleventh Five year Plan (2007-12), proposed research and extension strategies. Future scope and approach for improvement are some of the major issues highlighted in the present paper.